ASSESMENT OF PREVALENCE OF EXAMINATION MALPRACTICES AMONG UNIVERSITIES STUDENTS: A COMPARATIVE STUDY OF MALE AND FEMALE STUDENTS IN UNIVERSITIES IN MOUNT KENYA REGION - Meshack Ambani (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2020)
Stakeholders in education continue to express concerns regarding the proliferation of students' engagement in examination irregularities in universities in the world and Kenya in particular. Despite the stringent measures put in place to curb the vice, university students continue to engage in examination irregularities. The objectives of the study were; to assess the status of the prevalence of examination malpractices among university students in the Mt Kenya region, and to compare the prevalence of examination malpractices between male and female students in universities in the Mount Kenya region. The Ethical Theory guided the study. A descriptive research design was adopted. Kathuri and Pals' sampling table was used to sample 380 student participants. Data were collected using questionnaires. Cronbach Alpha Coefficient was calculated to establish the reliability of the instrument, which yielded r=0.79 thus higher than the 0.7 thresholds of acceptance. Experts from the department of education validated research instrument. Data analysis was descriptive and inferential statistics. Results showed that carrying unauthorized materials (50.4%), copying of answers (49.6%) and giraffing (50%) were the most prevalent forms of examination malpractices and students did not get leakages as indicated by 84.5% of respondents. The t-test yielded a p-value of 0.720 against the theoretical p = 0.05. The null hypothesis was accepted (at α =0.05). The engagement of male and female students in examination malpractice was relatively the same in universities under study. The study concluded that both gender engaged in examination malpractices. The study recommended that pragmatic measures were needed to control curb the menace.